Gridded bathymetry from EM120 multibeam echosounder of RV Maria S. Merian cruise MSM13-3 (Eastern Mediterranean Sea) - Wintersteller, Paul (PANGAEA, 2019)
Between 25.10. and 18.11.2009, Multibeam data based on the KONGSBERG Simrad EM120 were acquired during RV Maria S. Merian cruise MSM13/3.The investigation of diversity and community distribution of chemosynthetic ecosystems related to fluid escape structures at the eastern and central provinces of the Nile fan (Eastern Mediterranean Sea) was the main research target. Additionally element transport rates and fluid export related to these fluid seeps was further explored. This cruise was in corporation with the DIWOOD program. Therefore wood, which was deployed in 2006/2007, was recovered to investigate the influence of wood degradation on ecosystems. To collect gas/fluid and sediment samples, the ROV QUEST4000 (MARUM) was utilized. During the cruise hydroacoustic systems (Multibeam and Parasound) were recorded to generate high-resolution maps of the research areas as well as to identify and to quantify seepage structures. CI Citation: Paul Wintersteller (seafloor-imaging@marum.de) as responsible party for bathymetry raw data ingest and approval. Description of the data source: During the MSM13-3 cruise, the hull-mounted KONGSBERG EM120 multibeam echosounder (MBES) was utilized for bathymetric mapping in water depth beyond 1000 m as it allows accurate bathymetric mapping up to full ocean depth. Two linear transducer arrays in Mills Cross configuration transmit a nominal sonar frequency of 12 kHz with an maximum beam width of 130° across track and 1° along track. 191 individual beams were created per ping. The actual footprint of a beam has a dimension of 1° by 2°. On flat bottom, the achievable swath width can reach up to six times the water depth. The angular coverage sector and beam pointing angles were set to vary automatically with depth according to achievable coverage. For further information on the system, consult https://www.km.kongsberg.com/. Responsible person during this cruise / PI: Paul Wintersteller (pwintersteller@marum.de), Heiko Sahling and Miriam Römer (mroemer@marum.de). Description of data processing: Postprocessing and products were conducted by the Seafloor-Imaging & Mapping group of MARUM/FB5, responsible person: Paul Wintersteller (seafloor-imaging@marum.de). The post- processing was mainly done during the cruise using the Kongsberg Simrad Neptune Software as well as IVS Fledermaus. The open source software MB-System suite (Caress, D.W., and D.N. Chayes, MB-System Version 5.5, open source software distributed from the MBARI and L-DEO web sites, 2000-2012.) was utilized after the cruise for additional processing. Amplitude and sidescan corrections were applied for the MSM13-3 data. NetCDF (GMT) grids of the edited data as well as statitics were created with mbgrid. The published bathymetric grid of the cruise MSM13-3 has a resolution of 20 m. No total propagated uncertainty (TPU) has been calculated to gather vertical or horizontal accuracy. A higher resolution is, at least partly, achievable. The grid extended with _num represents a raster dataset with the statistical number of beams/depths taken into account to create the depth of the cell. The extended _sd -grid contains the standard deviation for each cell. All grids produced are retrievable through the PANGAEA database (www.pangaea.de). Chief Scientist: Antje Boetius CR: https://www.tib.eu/de/suchen/download/?tx_tibsearch_search%5Bdocid%5D=awi%3Adoi~10.2312%252Fcr_msm13_3&cHash=91ccabc6630ae9bbd4b3fc995f742237#download-mark CSR: https://www2.bsh.de/aktdat/dod/fahrtergebnis/2009/20100012.htm
Keywords: Bathymetry; Chemosynthetic Ecosystems; Eastern Mediterranean Sea; EM120; Flares; HOMER 1; hydroacoustic; ROV QUEST4000